Acid corrosion method for MLCC ceramic grains
By using an acid mixture of fluoroboric acid and hydrochloric acid to corrosion of MLCC ceramic capacitors, the problem of excessive corrosion of ceramic grains is solved, and high-accurate grain morphology and size analysis is achieved.
Patent Information
- Application Number
- CN202410896794.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-03-25
AI Technical Summary
The chemical corrosion methods of existing MLCC ceramic capacitors can easily lead to excessive corrosion of ceramic grains, affecting the accuracy of grain morphology and size analysis.
Corrosion is carried out using an acid mixture containing fluoroboric acid (HBF4) and hydrochloric acid (HCl) to control the corrosion time and concentration to prevent excessive corrosion of ceramic grains.
It effectively prevents excessive corrosion of ceramic grains, maintains high smoothness and flatness of grains, and ensures the accuracy of grain morphology and size analysis.
Smart Images

Figure CN119694784A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of multilayer ceramic capacitors, and more specifically, to an acid corrosion method for MLCC ceramic grains. Background Art
[0002] With the continuous advancement of information technology and digital technology of electronic products, electronic equipment is becoming increasingly miniaturized and lightweight. Multilayer ceramic capacitors (MLCC) are widely used in electronic equipment, and are gradually developing in the direction of miniaturization, high capacitance, high reliability and low price. As one of the important electronic components, the performance of MLCC will directly affect the overall function of electronic products.
[0003] Multilayer ceramic capacitors (MLCC) are composed of a substrate, internal electrodes, and terminal electrodes. They are divided into two categories: paraelectric (Class I) and ferroelectric (Class II) according to the different substrate ceramic dielectric materials used in MLCC. The substrate ceramic dielectric material used in Class I MLCC is barium strontium titanate (BaSrTiO3), and the substrate ceramic dielectric material used in Class II MLCC is barium titanate (BaTiO3). In the process of achieving high capacity, the substrate ceramic dielectric material used in MLCC will affect the reliability and capacity of the product, and the morphology and size of the grains of the substrate ceramic dielectric material are important factors affecting the performance of MLCC, including ceramic dielectric, piezoelectric, and ferroelectric.
[0004] When analyzing the morphology and size of the grains of the base ceramic dielectric material in MLCC, it is necessary to first corrode the MLCC to expose the grains of the base ceramic dielectric material, and then observe and analyze the morphology and size of the grains under a microscope. The methods of corroding MLCC include thermal corrosion and chemical corrosion. Thermal corrosion is to place the MLCC sample in a high-temperature furnace, and volatilize the grain boundary elements through high temperature, thereby exposing the grains of the base ceramic dielectric material for observation and analysis. Thermal corrosion takes a long time, is costly, inefficient, complicated to operate, and the corrosion conditions are difficult to explore. Chemical corrosion often uses HNO3, HCl, HF and their mixed acids to corrode MLCC samples, thereby exposing the grains of the base ceramic dielectric material for observation and analysis. Chemical etching takes a short time, is low-cost, and is easy to operate. It can process MLCC samples in batches with high efficiency. However, chemical etching often causes excessive corrosion of the ceramic grains of MLCC, which is manifested in poor smoothness of the ceramic grains, many grooves on the surface of the grains, and roughness; at the same time, the flatness of the ceramic grains is poor, the grains are uneven, and there are a large number of obvious depressions or pits between the grains. Excessive corrosion will affect the morphology and size of the grains, resulting in inaccurate analysis results, and it is impossible to accurately analyze the properties of MLCC, including ceramic dielectric, piezoelectric, and ferroelectric.
[0005] Therefore, it is of great significance to develop an acid etching method for MLCC ceramic grains that will not excessively corrode the ceramic grains. Summary of the invention
[0006] The purpose of the present invention is to solve the deficiencies of the prior art and to provide an acid corrosion method for MLCC ceramic grains.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] The present invention provides an acid corrosion method for MLCC ceramic grains, comprising the following steps:
[0009] S1. Polishing of multilayer ceramic capacitors (MLCC), exposing the inner electrodes, and the area where the inner electrodes are exposed is used as the polishing surface area of the MLCC;
[0010] S2. Corroding the polished surface area of the MLCC with an acid mixture to obtain a multilayer ceramic capacitor (MLCC) with exposed ceramic grains;
[0011] In step S2, the acid mixture contains fluoroboric acid (HBF4) and hydrochloric acid (HCl), the concentration of the fluoroboric acid (HBF4) is 4.0-11.5 mg / mL, and the concentration of the hydrochloric acid (HCl) is 8.0-45.0 mg / mL.
[0012] The acid corrosion method of MLCC ceramic grains of the present invention uses an acid mixture containing fluoroboric acid (HBF4) and hydrochloric acid (HCl) to corrode the MLCC to reveal the grain boundaries, thereby controlling the degree of chemical corrosion on the MLCC and preventing excessive corrosion of the MLCC ceramic grains. Specifically, the ceramic grains have high smoothness, and the surface of the grains has few or no grooves and is very smooth; at the same time, the ceramic grains have high flatness, the height of the grains is relatively consistent, and there are few or no obvious depressions or pits between the grains.
[0013] In addition, the acid corrosion method of the MLCC ceramic grains of the present invention will not corrode the internal electrodes of the MLCC, which is beneficial for subsequent analysis of the MLCC.
[0014] As a preferred embodiment of the acid corrosion method of MLCC ceramic grains of the present invention, the concentration of fluoroboric acid (HBF4) is 4.0-6.0 mg / mL.
[0015] As a further preferred embodiment of the acid corrosion method for MLCC ceramic grains of the present invention, the concentration of fluoroboric acid (HBF4) is 5.0-6.0 mg / mL, specifically 5.56 mg / mL.
[0016] As a preferred embodiment of the acid corrosion method of MLCC ceramic grains of the present invention, the concentration of the hydrochloric acid (HCl) is 22.0-45.0 mg / mL.
[0017] As a further preferred embodiment of the acid corrosion method of the MLCC ceramic grains of the present invention, the concentration of the hydrochloric acid (HCl) is 43.0-45.0 mg / mL, specifically 44.03 mg / mL.
[0018] The present invention can better control the degree of chemical corrosion on MLCC by controlling the concentration of fluoroboric acid (HBF4) and hydrochloric acid (HCl) in the acid mixture, thereby better preventing excessive corrosion of the ceramic grains of the MLCC and making the ceramic grains smoother and flatter.
[0019] As a preferred implementation of the acid corrosion method for MLCC ceramic grains of the present invention, in step S2, the corrosion time is 3-10s.
[0020] As a further preferred embodiment of the acid corrosion method for MLCC ceramic grains of the present invention, in step S2, the corrosion time is 3-5s.
[0021] The present invention can better control the degree of chemical corrosion on MLCC by controlling the corrosion time of the acid mixture, thereby better preventing excessive corrosion of the ceramic grains of the MLCC and making the ceramic grains smoother and flatter.
[0022] In the acid etching method of the present invention, the etching temperature in step S2 is room temperature, which is 10-40°C, and can be specifically 25°C.
[0023] As a preferred embodiment of the acid etching method for MLCC ceramic grains of the present invention, in step S2, the etching method is to drip the acid mixture onto the polishing surface area of the MLCC.
[0024] As a further preferred embodiment of the acid etching method for MLCC ceramic grains of the present invention, the amount of the acid mixture is 1.25-6.25 mL of the acid mixture per square centimeter of the polishing surface area.
[0025] As a preferred embodiment of the acid etching method for MLCC ceramic grains of the present invention, in step S2, after etching the polished surface area of the MLCC with the acid mixture, it also includes cleaning the polished surface area with a cleaning agent.
[0026] As a further preferred embodiment of the acid etching method for MLCC ceramic grains of the present invention, the cleaning agent contains at least one of water and ethanol.
[0027] As a preferred embodiment of the acid corrosion method of the MLCC ceramic grains of the present invention, in step S1, the polishing of the laminated ceramic capacitor (MLCC) is performed by sequentially polishing the laminated ceramic capacitor (MLCC) with 600-800 mesh sandpaper, 1200 mesh sandpaper, 2400-2500 mesh sandpaper, 4000 mesh sandpaper, and polishing flannel cloth.
[0028] As a further preferred embodiment of the acid corrosion method of the MLCC ceramic grains of the present invention, in step S1, the polished laminated ceramic capacitor (MLCC) is polished by 800 mesh sandpaper, 1200 mesh sandpaper, 2500 mesh sandpaper, 4000 mesh sandpaper, and polishing flannel cloth in sequence.
[0029] As a preferred embodiment of the acid etching method for MLCC ceramic grains of the present invention, in step S1, before polishing the multilayer ceramic capacitor (MLCC), it also includes embedding the multilayer ceramic capacitor (MLCC) in resin and curing it.
[0030] In the present invention, the resin used to cure MLCC is a conventional resin in the art, such as at least one of epoxy resin, phenolic resin, urea-formaldehyde resin, melamine formaldehyde resin, furan resin, silicone resin, polyester resin, polyamide resin, acrylic resin, polyurethane, vinyl resin, hydrocarbon resin, polyether resin, etc.
[0031] As a preferred embodiment of the acid corrosion method of MLCC ceramic grains of the present invention, in step S1, the base ceramic dielectric material used by the multilayer ceramic capacitor (MLCC) is barium strontium titanate, that is, the multilayer ceramic capacitor (MLCC) is a paraelectric (Class I) MLCC.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The acid corrosion method of MLCC ceramic grains of the present invention uses an acid mixture containing fluoroboric acid (HBF4) and hydrochloric acid (HCl) to corrode the MLCC to reveal the grain boundaries, thereby controlling the degree of chemical corrosion on the MLCC and preventing excessive corrosion of the MLCC ceramic grains. Specifically, the ceramic grains have high smoothness, and the surface of the grains has few or no grooves and is very smooth; at the same time, the ceramic grains have high flatness, the height of the grains is relatively consistent, and there are few or no obvious depressions or pits between the grains.
[0034] In addition, the acid corrosion method of the MLCC ceramic grains of the present invention will not corrode the internal electrodes of the MLCC, which is beneficial for subsequent analysis of the MLCC.
[0035] In addition, compared with the use of an acid mixture containing nitric acid and hydrochloric acid, the acid mixture containing fluoroboric acid (HBF4) and hydrochloric acid (HCl) selected by the acid etching method of the present invention can more quickly display the morphology of ceramic grains, controllably avoid excessive corrosion of ceramic grains, and is easier to operate. Moreover, the acid etching method of MLCC ceramic grains of the present invention does not require ion grinding and polishing pre-treatment of MLCC, and can process MLCC in batches, which has the advantage of high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Figure 1 is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Examples 1-2 and Comparative Examples 1-2, wherein Figure A is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Example 1, Figure B is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Example 2, Figure C is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Comparative Example 1, and Figure D is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Comparative Example 2.
[0037] Figure 2 Figure 1 is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Example 1 and Comparative Examples 3-6, wherein Figure A is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Example 1, Figure B is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Comparative Example 3, Figure C is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Comparative Example 4, Figure D is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Comparative Example 5, and Figure E is an SEM image of the MLCC polished surface area where ceramic grains are exposed in Comparative Example 6.
[0038] Figure 3 The SEM images of the polished surface area of the MLCC where ceramic grains are exposed in Example 1, Example 8 and Comparative Example 10, wherein Figure A is a SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Example 8, Figure B is a SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Example 1, and Figure C is a SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Comparative Example 10.
[0039] Figure 4 This is the SEM image of the polished surface area of the MLCC in comparative example 7 where the ceramic grains are exposed.
[0040] Figure 5 These are SEM images of the polished surface area of the MLCC where ceramic grains are exposed in Comparative Examples 8-9. Figure A is an SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Comparative Example 8, and Figure B is an SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Comparative Example 9.
[0041] Figure 6This is the SEM image of the polished surface area of the MLCC where the ceramic grains are exposed in Comparative Example 11.
[0042] Figure 7 This is the SEM image of the polished surface area of the MLCC in comparative example 12 where the ceramic grains are exposed. DETAILED DESCRIPTION
[0043] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0044] Example 1
[0045] This embodiment provides an acid etching method for MLCC ceramic grains, comprising the following steps:
[0046] S1. Embed 5 multilayer ceramic capacitors (MLCCs) in epoxy resin for curing, wherein the LT surface of the MLCC (the vertical surface of the long axis stacking surface of the MLCC, also called the electrode surface) is close to the surface of the mold, and the LT surface of the multilayer ceramic capacitor (MLCC) is polished to a mirror surface with 800-grit sandpaper, 1200-grit sandpaper, 2500-grit sandpaper, 4000-grit sandpaper, and polishing flannel cloth in sequence to expose the inner electrode, and the area where the inner electrode is exposed is used as the polishing surface area of the MLCC;
[0047] S2. Take 1.390g of 40% fluoroboric acid (HBF4) and 11.900g of 37% hydrochloric acid (HCl) in a 100mL volumetric flask, adjust the volume to obtain an acid mixed solution with a HBF4 concentration of 5.56mg / mL and a HCl concentration of 44.03mg / mL; in a fume hood at 25°C, drop the acid mixed solution on the polished surface area of MLCC for corrosion for 5s, clean the polished surface area with ultrapure water, then put it in ultrapure water for ultrasonic treatment for 1min, and then clean the multilayer ceramic capacitor (MLCC) 3 times with ultrapure water and ethanol alternately to obtain a multilayer ceramic capacitor (MLCC) with exposed ceramic grains, and finally use a scanning electron microscope (SEM) to photograph the morphology of the polished surface area of MLCC;
[0048] The base ceramic dielectric material used in the multilayer ceramic capacitor (MLCC) is barium strontium titanate, that is, the multilayer ceramic capacitor (MLCC) is a paraelectric (Class I) MLCC;
[0049] The amount of the acid mixture is 1.50 mL per square centimeter of the polishing surface area.
[0050] Examples 2-8 and Comparative Examples 1-10
[0051] Examples 2-8 and Comparative Examples 1-10 provide different acid etching methods for MLCC ceramic grains, which differ from Example 1 in that the concentration of fluoroboric acid in the acid mixture, the concentration of hydrochloric acid, and the etching time of the acid mixture are different, and the rest are consistent with Example 1, as shown in the following table:
[0052] Table 1 Concentrations of fluoroboric acid and hydrochloric acid in the acid mixtures of Examples 1-8 and Comparative Examples 1-10 and corrosion time
[0053]
[0054]
[0055] Comparative Example 11
[0056] This comparative example provides an acid corrosion method for MLCC ceramic grains. The difference between the comparative example and Example 1 is that hydrofluoric acid (HF) is used instead of fluoroboric acid. The rest is consistent with Example 1. It is worth noting that in the acid mixed solution, the concentration of HF is 5.56 mg / mL and the concentration of HCl is 44.03 mg / mL.
[0057] Comparative Example 12
[0058] This comparative example provides an acid corrosion method for MLCC ceramic grains. The difference between this comparative example and comparative example 11 is that hydrochloric acid (HCl) is not used. The rest is consistent with comparative example 11. It is worth noting that there is only HF in the acid mixed solution, and the concentration of HF is 5.56 mg / mL.
[0059] Sample characterization
[0060] The morphology of the polished surface area of the multilayer ceramic capacitor (MLCC) with exposed ceramic grains in each embodiment and comparative example was characterized by a scanning electron microscope (SEM).
[0061] Figure 1 The SEM images of the polished surface area of the MLCC with ceramic grains exposed in Examples 1-2 and Comparative Examples 1-2 are shown, wherein Figure A is a SEM image of the polished surface area of the MLCC with ceramic grains exposed in Example 1, Figure B is a SEM image of the polished surface area of the MLCC with ceramic grains exposed in Example 2, Figure C is a SEM image of the polished surface area of the MLCC with ceramic grains exposed in Comparative Example 1, and Figure D is a SEM image of the polished surface area of the MLCC with ceramic grains exposed in Comparative Example 2. The SEM images of the polished surface area of the MLCC with ceramic grains exposed in Examples 3-4 are similar to those in Example 1. Figure 1 A is similar.
[0062] from Figure 1It can be seen that when the concentration of HBF4 in the acid mixed solution is fixed at 5.56 mg / mL, the concentration of HCl is 22.0-45.0 mg / mL, especially in the range of 43.0-45.0 mg / mL, the acid corrosion method of the present invention can better control the degree of chemical corrosion on MLCC, and better prevent excessive corrosion of the ceramic grains of MLCC, which is specifically manifested in that the ceramic grains are smoother, and there are no or fewer grooves on the surface of the grains, which are very smooth; at the same time, the ceramic grains have higher flatness, the height of the grains is more consistent, and there are no or fewer obvious depressions or pits between the grains.
[0063] Figure 2 The SEM images of the polished surface area of the MLCCs exposing ceramic grains in Example 1 and Comparative Examples 3-6 are shown, wherein Figure A is a SEM image of the polished surface area of the MLCCs exposing ceramic grains in Example 1, Figure B is a SEM image of the polished surface area of the MLCCs exposing ceramic grains in Comparative Example 3, Figure C is a SEM image of the polished surface area of the MLCCs exposing ceramic grains in Comparative Example 4, Figure D is a SEM image of the polished surface area of the MLCCs exposing ceramic grains in Comparative Example 5, and Figure E is a SEM image of the polished surface area of the MLCCs exposing ceramic grains in Comparative Example 6. The SEM images of the polished surface areas of the MLCCs exposing ceramic grains in Examples 5-7 are similar to those in Example 1. Figure 2 A is similar.
[0064] from Figure 2 It can be seen that when the concentration of HCl in the acid mixed solution is fixed at 44.03 mg / mL, the concentration of HBF4 is 4.0-6.0 mg / mL, especially in the range of 5.0-6.0 mg / mL, the acid corrosion method of the present invention can better control the degree of chemical corrosion on MLCC, and better prevent excessive corrosion of the ceramic grains of MLCC, which is specifically manifested in that the ceramic grains are smoother, and there are no or fewer grooves on the surface of the grains, which are very smooth; at the same time, the ceramic grains have higher flatness, the height of the grains is more consistent, and there are no or fewer obvious depressions or pits between the grains.
[0065] Figure 3 The SEM images of the polished surface area of the MLCC where ceramic grains are exposed in Example 1, Example 8 and Comparative Example 10, wherein Figure A is a SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Example 8, Figure B is a SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Example 1, and Figure C is a SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Comparative Example 10.
[0066] from Figure 3It can be seen that when the corrosion time of the acid mixture on the polishing surface area of MLCC is controlled to be 3-5s, especially 5s, the acid corrosion method of the present invention can better control the corrosion degree of chemical corrosion on MLCC, and better prevent excessive corrosion of the ceramic grains of MLCC. Specifically, the ceramic grains are smoother, and there are no or fewer grooves on the surface of the grains, which are very smooth; at the same time, the ceramic grains have higher flatness, the height of the grains is more consistent, and there are no or fewer obvious depressions or pits between the grains.
[0067] Figure 4 This is the SEM image of the polished surface area of the MLCC in comparative example 7 where the ceramic grains are exposed. Figure 5 These are SEM images of the polished surface area of the MLCC where ceramic grains are exposed in Comparative Examples 8-9. Figure A is an SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Comparative Example 8, and Figure B is an SEM image of the polished surface area of the MLCC where ceramic grains are exposed in Comparative Example 9. Figure 6 This is the SEM image of the polished surface area of the MLCC where the ceramic grains are exposed in Comparative Example 11. Figure 7 This is the SEM image of the polished surface area of the MLCC in comparative example 12 where the ceramic grains are exposed.
[0068] By comparison Figure 1 and Figure 4-7 It can be seen that when only fluoroboric acid, hydrochloric acid or hydrofluoric acid is selected, or when a combination of hydrofluoric acid and hydrochloric acid is selected, the acid corrosion method of the present invention cannot control the degree of chemical corrosion on MLCC, and cannot prevent excessive corrosion of the ceramic grains of MLCC; in particular, when only hydrochloric acid is selected in Comparative Example 9 and the corrosion time is extended from 5s to 900s (i.e., 15min), the ceramic grain structure of the MLCC can no longer be observed, indicating that the MLCC ceramic grains are severely corroded.
[0069] In addition, compared with the comparative example 12 using only HF, the comparative example 11 using the combination of HF and HCl has a higher flatness of the ceramic grains, the height of the grains is more consistent, and there are fewer obvious depressions or pits between the grains. This is because Cl - With F - There is competitive adsorption between Cl - Will hinder F - Deep corrosion on the surface of ceramic grains makes fewer obvious depressions or pits appear between grains; at the same time, Cl - With F - The competitive adsorption between them will cause the acid mixture to corrode the surface of the ceramic grains evenly, resulting in poor smoothness of the ceramic grains in Comparative Example 11, with many grooves and roughness on the surface of the grains.
[0070] Compared with Comparative Example 11 using the combination of HF and HCl, Example 1 using the combination of HBF4 and HCl, due to the slow hydrolysis of HBF4, the acid corrosion method of the present invention can better control the degree of chemical corrosion on MLCC and better prevent excessive corrosion of the ceramic grains of MLCC, which is specifically manifested in that the ceramic grains are smoother, and there are no or fewer grooves on the surface of the grains and they are very smooth; at the same time, the ceramic grains have higher flatness, the height of the grains is more consistent, and there are no or fewer obvious depressions or pits between the grains.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An acid corrosion method for MLCC ceramic grains, characterized in that: The steps include: S1. Polishing the multilayer ceramic capacitor to expose the inner electrode, and the area with the exposed inner electrode is used as the polishing surface area of MLCC; S2. Corroding the polished surface area of MLCC with an acid mixture to obtain a multilayer ceramic capacitor with exposed ceramic grains; In step S2, the acid mixture contains fluoroboric acid and hydrochloric acid, the concentration of the fluoroboric acid is 4.0-11.5 mg / mL, and the concentration of the hydrochloric acid is 8.0-45.0 mg / mL.
2. The acid etching method for MLCC ceramic grains according to claim 1, characterized in that: The concentration of the fluoroboric acid is 4.0-6.0 mg / mL.
3. The acid etching method for MLCC ceramic grains as claimed in claim 2, characterized in that: The concentration of the fluoroboric acid is 5.0-6.0 mg / mL.
4. The acid etching method for MLCC ceramic grains according to claim 1, characterized in that: The concentration of the hydrochloric acid is 43.0-45.0 mg / mL.
5. The acid etching method for MLCC ceramic grains according to claim 1, characterized in that: In step S2, the corrosion time is 3-10s.
6. The acid etching method for MLCC ceramic grains as claimed in claim 5, characterized in that: In step S2, the corrosion time is 3-5s.
7. The acid etching method for MLCC ceramic grains according to claim 1, characterized in that: In step S2, the etching method is to drop the acid mixture on the polishing surface area of the MLCC.
8. The acid etching method for MLCC ceramic grains according to claim 1, characterized in that: The amount of the acid mixture is 1.25-6.25 mL per square centimeter of the polishing surface area.
9. The acid etching method for MLCC ceramic grains according to claim 1, characterized in that: In step S2, after the polished surface area of the MLCC is corroded with the acid mixture, the polished surface area is cleaned with a cleaning agent.
10. The acid etching method for MLCC ceramic grains according to claim 1, characterized in that: In step S1, the grinding and polishing of the multilayer ceramic capacitor is performed by sequentially using 600-800 mesh sandpaper, 1200 mesh sandpaper, 2400-2500 mesh sandpaper, 4000 mesh sandpaper, and polishing flannel cloth.